A Review of Musical Content Creativity in the Vocal Groove Community - Adelya Annisa Marfirasari (Universitas Negeri Surabaya, 2026)
This study aims to describe in depth the various stages of the creative process undertaken by Vocal Groove in creating music content, as well as to analyze creative solutions to overcome constraints in creating music content. This study uses qualitative methods, with data collection based on observation of Vocal Groove content on TikTok, in-depth interviews with members and the founder of the Vocal Groove community, and supporting documentation. This research examines the creative process of the Vocal Groove community in creating music content on TikTok, focusing on the case study